Novel Fabrication Technique to Confine Hydrogels with Different Patterns inside Microfluidic Devices without Pillars - Olaizola Rodrigo, Claudia; Bayona, Clara; Pérez, Marina; Doblaré, Manuel; Monge, Rosa; Oliván, Sara; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2022)
In the field of microtechnologies applied to the simulation of controlled biological environments are the so-called organ-on-a-chip, microfluidic cell culture devices. The gradient model plays an indispensable role in this technology. Here, we present a novel microfabrication process for pillarless microfluidic platforms which enables the creation of gradients inside them.